Meaning in transition: A didactic–hermeneutic inquiry into how the concept of variables transposed from teaching to student understanding - Nadya Syifa Utami; Hafsah Adha Diana; Sani Sahara; Phoong Seuk Yen (Universitas Sarjanawiyata Tamansiswa, 2025)
The concept of variable is central to algebraic thinking, yet many students struggle to understand it due to how it is introduced in classroom practice. This study investigates the didactic transposition of the meaning of variable from the knowledge intended by the teacher to the knowledge constructed by students. Employing a qualitative approach grounded in the Anthropological Theory of the Didactic (ATD) and hermeneutic analysis, the study examines teaching materials, teacher and student interviews, and students’ written assessments in a junior high school context. The findings reveal an epistemic shift in the meaning of variable: although the teacher intended to introduce variables as unknown quantities within algebraic relationships, classroom instruction predominantly emphasized symbolic manipulation and procedural equation solving. As a result, students interpreted variables as static placeholders for fixed values rather than as quantities that can vary. This led to a restricted, object-based understanding of variables, limiting students’ ability to engage with generalization and relational reasoning. The study concludes that prevailing didactical practices unintentionally simplify and constrain the conceptual richness of variables. This study contributes to the field of mathematics education by advocating for a pedagogical shift that explicitly bridges procedural equation solving with the dynamic and varying nature of algebraic reasoning.